A Controlled Trial of a Cognitive Skills Program for Personality-Disordered Offenders. (October 2013) - Young, Susan; Hopkin, Gareth; Perkins, Derek; Farr, Catherine; Doidge, Amie; Gudjonsson, Gisli
Objective : There is a need to find effective treatments for individuals with antisocial and borderline personality disorder who are known to be difficult to engage and treat. Many of these individuals share considerable overlap with symptoms of ADHD, hence this study aimed to evaluate the Reasoning and Rehabilitation ADHD program (R&R2 ADHD) among patients with severe personality disorder.Method : A total of 31 males detained in a "dangerous and severe personality disorder" unit completed questionnaires at baseline and post treatment to assess social problem solving, violent attitudes, anger, ADHD symptoms, emotional control, and social functioning. A total of 16 patients participated in the group condition, and their scores were compared with 15 waiting-list controls who received treatment as usual.Results : In all, 76% of group participants completed the program. In contrast to controls, they showed significant improvements in scores with mainly medium effect sizes.Conclusion : R&R2 ADHD was effective in a small sample of severely personality-disordered offenders.